Pigmented Villonodular Synovitis of the Hip Managed with Arthroscopic Synovectomy: An Analysis of 19 Cases with up to 10-year Follow-up. Issue 7 (29th July 2019) - Nazal, Mark R.; Stelzer, John W.; Parsa, Ali; Discuillo, Alex A.; Agrawal, Ravi; Martin, Scott D.
Objectives: A tenosynoival giant cell tumor known as pigmented villonodular synovitis (PVNS) is a rare, benign, yet locally aggressive neoplasm arising from the synovium. Although most frequently encountered in the knee joint, PVNS is secondly most commonly seen in the hip joint. Occurrence of PVNS in the hip may destroy intra-articular soft tissue and bone, and at times invade extra-articular tissues. There are two categorizations of PVNS: localized and diffuse. The localized manifestation, often referred to as nodular, involves a focal or limited area of the synovium, while the diffuse manifestation involves more widespread areas throughout the synovium. Surgical management by resection of the PVNS within the hip joint has been described with open procedures and arthroscopic procedures. Although surgical management has been shown to be promising, PVNS has a high recurrence rate, of 15-50%. To date, we present the largest cohort of hip joint PVNS managed by arthroscopic synovectomy with mid-term follow-up. Methods: A cohort of 19 patients were diagnosed with hip PVNS and underwent arthroscopic synovectomy between 2008 and 2016. Patients were identified preoperatively based on suspected MRI findings of PVNS or intraoperatively after unexpected PVNS was identified during arthroscopy for another pathology. We assessed patients' functional ability at a minimum of 2-years follow-up using five patient reported outcome measures (PROMs): mHHS (modified Harris Hip Score), HOS (Hip Outcome Score), iHOT-33 (international Hip Outcome Tool), NAHS (Non-Arthritic Hip Score), and LEFS (Lower Extremity Functional Score). Results: Nineteen patients with hip PVNS were treated with an arthroscopic hip synovectomy. Sixteen of the patients completed patient reported outcome measures. This cohort consisted of 7 (44%) females and 9 (56%) males. The mean patient age was 37 years (range, 25-54). Mean follow-up was 83 months (6.9 years), ranging from 24 months (2 years) to 123 months (10.3 years). Eight (50%) patients had diffuse PVNS and 8 (50%) of patients had nodular PVNS. Laterality of the arthroscopic procedure was 8 (50%) right hip and 8 (50%) left hip. Five (31%) of the patients had a smoking history, while 11 (69%) were non-smokers. Four (25%) had a cam lesion, 4 (25%) had a pincer lesion, 8 (50%) had neither cam nor pincer lesion, and 0 (0%) had combined cam and pincer lesion. Fourteen (88%) patients had histologically confirmed PVNS. Eleven (69%) patients had MRI suspected PVNS prior to arthroscopy, while 5 (31%) patients had unexpected PVNS discovered intraoperatively. Concomitant pathology addressed at the time of arthroscopy, includes 11 (79%) labral tear repair. For the sixteen patients that completed patient reported outcome measures, the mean mHHS was 78.2 (SD, 10.6). Mean HOS-ADL was 10 (SD, 10). Mean HOS-SSS was 21 (SD, 20). Mean iHOT-33 was 69.4 (SD, 16.3). Mean NAHS was 86.5 (SD, 10.2). Mean LEFS was 70.8 (SD, 7.7). A mean percentage of maximal function was 88.6% (SD, 9.8%). To date, 0 (0%) patients have shown evidence of recurrence upon physical exam, follow-up MRI, or repeat arthroscopy. Conclusion: Based on the largest arthroscopically managed cohort of PVNS in the hip to date, we conclude that arthroscopic synovectomy is a reliable and effective treatment of hip PVNS. Patients reported good functional outcomes without evidence of recurrence in a 19 patient cohort with an average follow-up of almost 7 years.